Assessment and outcome of children with intestinal failure referred for intestinal transplantation. Issue 3 (June 2015) - Ganousse-Mazeron, S.; Lacaille, F.; Colomb-Jung, V.; Talbotec, C.; Ruemmele, F.; Sauvat, F.; Chardot, C.; Canioni, D.; Jan, D.; Revillon, Y.; Goulet, O.
Summary Background & aims Chronic intestinal failure (CIF) requires long term parenteral nutrition (PN) and, in some patients, intestinal transplantation (ITx). Indications and timing for ITx remain poorly defined. In the present study we aimed to analyze causes and outcome of children with CIF. Methods 118 consecutive patients referred to our institution were assessed by a multidisciplinary team and four different categories were defined retrospectively based on their clinical course: Group 1: patients with reversible intestinal failure; group 2: patients unsuitable for ITx, group 3: patients listed for ITx; group 4: patients stable under PN. Analysis involved comparison between groups for nutritional status, central venous catheter (CVC) related complications, liver disease, and outcome after transplantation by using non parametric tests, Mann–Whitney tests, Kruskal–Wallis, Wilcoxon signed rank tests and chi square distribution for percentage. Results 118 children (72 boys) with a median age of 15 months at referral (2 months–16 years) were assessed. Etiology of IF was short bowel syndrome [n = 47], intractable diarrhea of infancy [n = 37], total intestinal aganglionosis [n = 18], and chronic intestinal pseudoobstruction [n = 17]. Most patients (89.8%) were totally PN dependent, with 48 children (40.7%) on home-PN prior to admission. Nutritional status was poor with a median body weight at −1.5 z-score (ranges: −5 to +2.5) and median length at −2.0 z-score (ranges: −5.5 to +2.3). The mean number of CVC inserted per patient was 5.2 (range 1–20) and the mean number of CRS per patient was 5.5 (median: 5; range 0–12) Fifty-five patients (46.6%) had thrombosis of ≥2 main venous axis. At admission 34.7% of patients had elevated bilirubin (≥50 μmol/l), and 19.5% had platelets <100, 000/ml, and 15% had both. Liver biopsy performed in 79 children was normal (n = 4), or showed F1 or F2 fibrosis (n = 29), bridging fibrosis F3 (n = 20), or cirrhosis (n = 26). Group 1 included 10 children finally weaned from PN (7-years survival: 100%). Group 2 included 12 children with severe liver disease and associated disorders unsuitable for transplantation (7-years survival: 16.6%). Group 3 included 66 patients (56%) who were listed for small bowel or liver-small bowel transplantation, 62/66 have been transplanted (7years survival: 74.6%). Factors influencing outcome after liver-ITx were body weight (p < .004), length (p < .001), pre-Tx bilirubin plasma level (p < .001) and thrombosis (p < .01) for isolated ITx, Group 4 included 30 children (25.4%) with irreversible IF considered as potential candidates for isolated ITx. Four children were lost from follow up and 3 died within 2 years (survival 88.5%). Among potential candidates, the following parameters improved significantly during the first 12 months of follow up: Body weight (p.0001), length (p < .0001) and bilirubin (p < .0001). Conclusions many patients had a poor nutritional status with severe complications especially liver disease. PN related complications were the most relevant indication for ITx, but also a negative predictor for outcome. Early patient referral for Tx-assessment might help to identify and separate children with irreversible IF from children with transient IF or uncomplicated long-term PN, allowing to adapt a patient-based treatment strategy including or not ITx.